Assigning femininity: The use of gendered second- and third-person pronouns in contemporary Chinese - Kansa, Maari (My University, 2024)
This Bachelor's Thesis investigates the use of second- and third-person pronouns in written Chinese and the attitudes speakers have towards their use in situations where the referent is a woman. The use of gendered pronouns in Chinese and the interaction between these pronouns and gender roles has been researched sparsely. Therefore, this thesis acts as an initiator for further discussion and research into the topic. The goal of this research is to take a step towards a more holistic understanding of changes in the use of gendered Chinese pronouns in addition to researching the interaction between written Chinese and the gender identities of its speakers. Based on the gathered data and with the support of preexisting research, we will also be able to discuss the significance and implications of gendered language in a broader context. The data of this thesis consists of answers and texts provided by female native speakers of Chinese, who filled out an online form, composed short sample texts, and took part in a voluntary interview. With the gathered data, we have reached a preliminary understanding of the usage patterns of Chinese personal pronouns and attitudes towards them in the context of female speakers. The received answers and sample texts indicate that the attitudes of young Chinese-speaking women are laxer and more progressive than the traditionally accepted rules. They also convey differences in the usage habits of Taiwanese and mainland Chinese speakers. Taiwanese participants were more likely to accept the use of the Chinese characters "你" (second-person pronoun) and "他" (third-person pronoun) to refer to referents assumed female, despite these two characters implying both masculine and neutral gender. In addition, the interviewees mentioned that they had noticed that many people chose to not differentiate genders in their informal written texts because of "laziness", since it takes additional effort to choose the right Chinese character when writing a text digitally. These findings indicate that there are variations among contemporary users of Mandarin Chinese that clearly differentiate from the traditional rules of gendered pronoun use. It would be beneficial to further investigate this topic to arrive at a clearer understanding of the attitudes towards gendered language among Mandarin Chinese speakers and the changes happening in the language itself.

Tässä kandidaatintutkielmassa perehdytään kirjoitetun kiinan kielen toisen ja kolmannen persoonan pronominien käyttöön ja käyttöön liittyviin asenteihin tilanteissa, joissa viitataan naispuoliseen henkilöön. Sukupuolitettujen persoonapronominien käyttöä ja niiden vuorovaikutusta sukupuoliroolien kanssa ei ole vielä kattavasti kartoitettu, joten tämä tutkielma toimii keskustelun aloittajana ja mahdollisena pohjana tulevalle laajemmalle tutkimukselle. Tutkimuksen tavoitteena on päästä lähemmäs kokonaisvaltaista ymmärrystä kirjoitetun kiinan ja kiinan puhujien sukupuoli-identiteetin vuorovaikutuksesta ja pronominien käytössä tapahtuneista muutoksista. Kerättyjen materiaalien ja muiden alan tutkimusten pohjalta voimme pohtia myös sukupuolitetun kielen merkitystä yleisesti. Tätä tutkielmaa varten äidinkieliset naispuoliset vastaajat täyttivät internetin kautta kyselyn, tuottivat itse lyhyitä esimerkkitekstejä ja osallistuivat vapaaehtoiseen haastatteluun, josta saatujen tietojen avulla saamme alustavan käsityksen persoonapronominien käyttöön liittyvistä tavoista ja asenteista naisten keskuudessa. Kyselyn, esimerkkitekstien ja haastattelujen pohjalta saatu käsitys persoonapronominien käytöstä osoittaa kiinankielisten nuorten naisten asenteen olevan selkeästi perinteisesti hyväksyttyjä sääntöjä rennompi ja progressiivisempi, ja viittaa eroihin käyttötavoissa kiinalaisten ja taiwanilaisten puhujien välillä. Etenkin taiwanilaisten osallistujien keskuudessa sukupuolineutraalien sekä samanaikaisesti maskuliinisten kirjoitusmerkkien “你” (2. persoona) ja ”他” (3. persoona) katsotaan sopivan toisen ja kolmannen persoonan pronomineiksi myös silloin, kun niitä käytetään viittaamaan selkeästi naispuolisiin henkilöihin. Haastatteluihin osallistuneet henkilöt kertoivat myös huomanneensa, että epävirallisessa kontekstissa monet tekstin tuottajat “ovat laiskoja” ja välttävät feminiinien pronominien käyttöä, sillä niitä varten kirjoittaja joutuu erikseen valitsemaan oikean kirjoitusmerkin näppäimistön tarjoamista vaihtoehdoista. Nämä löydöt osoittavat nykypäivän kiinankielisten puhujien keskuudessa olevan variaatiota ja selkeitä poikkeamia perinteisiin sääntöihin verrattaessa. Jotta kuva kiinan kielen muutoksista ja sen puhujien näkökulmista tulisi selkeämmäksi, olisi aiheesta tarpeen tehdä tätä tutkielmaa kattavampia jatkotutkimuksia.
Keywords: gender pronouns, gender identity, Chinese pronouns, sociolinguistics